Sensitivity Analysis of Noah-MP Model Parameterization Schemes for Soil Moisture Simulation in the High-Cold Region of the Upper Heihe River Basin - Kexiu HUANG; Yuanhong YOU; Yanyu LU; Ying HAO; Zuo WANG; Jing SUN (Gaoyuan qixiang, 2025)
In the context of climate change， accurately simulating soil moisture using land surface process models holds significant importance for weather forecasting， agricultural production， and hydrological processes.This study utilized meteorological observation data from the Arou site in the upper reaches of the Heihe River as the driving data for the Noah-MP model to conduct soil moisture simulation experiments， aiming to assess the soil moisture simulation performance of the Noah-MP model in the alpine mountainous area of the upper reaches of the Heihe River.Without considering uncertainties in model parameters and driving data， arbitrary combinations of the parameterization schemes for different physical processes of the Noah-MP model were made.A soil moisture multi-parameterization ensemble simulation experiment encompassing 17， 280 different combination schemes was designed.The Natural Selection sensitivity analysis method was employed to analyze the sensitivity of shallow soil moisture simulation results to the parameterization schemes and further quantify the uncertainty range of the simulation results of the soil moisture multi-parameterization ensemble.The results of this research indicate that the Noah-MP model can be applied to simulate soil moisture in the alpine mountainous area of the upper reaches of the Heihe river basin.The model demonstrates relatively high accuracy in simulating shallow soil moisture， and the simulated soil moisture change trends are generally consistent with the observed data.This consistency suggests that the Noah-MP model is well-suited for capturing the dynamics of shallow soil moisture in these regions.However， the simulation accuracy for deep soil moisture is relatively poor， with the simulated soil moisture change trends showing considerable deviations from the observed data.This suggests that there are still challenges in accurately modeling moisture dynamics at greater soil depths， potentially due to the complexity of subsurface hydrological processes in cold and mountainous environments.The analysis also reveals that shallow soil moisture simulation results are sensitive to the parameterization schemes of four physical processes： supercooled liquid water in frozen soil， frozen soil permeability， partitioning precipitation into rainfall and snowfall， and the first-layer snow or soil temperature time scheme.Among these， the parameterization scheme of frozen soil permeability is particularly sensitive， indicating that it plays a crucial role in determining the accuracy of the simulation results.During the soil freeze-thaw cycle in the alpine mountainous area of the upper reaches of the Heihe River， the simulation results of soil moisture during the freezing period showed increased sensitivity to parameterization schemes， making the selection of the parameterization scheme for the soil freezing process the main factor contributing to the uncertainty of the simulation results of the soil moisture multi-parameterization ensemble.